Investigating the Influence of Financial Indicators on Stock Returns in the Presence of the COVID-19 Pandemic - Almansour, Ammar Yaser; Hasan, Elina F; Matar, Ghassan Ahmad Abu; Almansour, Yaser Mansour; Haddad, Hossam (Asian Economic and Financial Review, 2022)
In this paper, we investigate the influence of financial proxies on companies in the real estate sector listed on the Amman stock exchange during the Covid-19 pandemic. A panel data method is employed for the sample, which includes 29 listed real estate companies, for the period from 2010 to 2020. The financial proxies are considered as independent variables, which consist of earnings per share, book value per share, price-to-earnings (P/E) ratio, price-to-book value, debt ratio, and current ratio, while the market return is the dependent variable. The results revealed that all financial proxies have a significant impact on market returns. Furthermore, the financial proxies are positively and significantly correlated with market returns. The results also showed that the Covid-19 pandemic negatively affected the real estate sector returns. Decision makers in real estate companies are required to manage their working capital in an effective and efficient manner in order to deal with unforeseen short-term events as investors might use historical financial data to estimate companies’ returns.